Bioactive foods in promoting health fruits and vegetables - Watson, Ronald R.; Preedy, Victor R. (Academic, 2010)
While everyone knows fruits and vegetables are beneficial to good health, it's increasingly seen as important to know which ones can be effective in treating specific illnesses. For example, which are good for cardiac care? Which can help combat and treat asthma? What are the safety concerns to be aware of when using herbs in combination with traditional medicines? Diet and nutrition are vital keys to controlling or promoting morbidity and mortality from chronic diseases, and the multitude of biomolecules in dietary fruits and vegetables play a crucial role in health maintenance. They may, therefore, be more effective and certainly could have different actions beyond nutrients however this science is still evolving. This book brings together experts working on the different aspects of supplementation, foods, and plant extracts, in health promotion and disease prevention. Their expertise and experience provide the most current knowledge to promote future research.-Dietary habits need to be altered, for most people and the conclusions and recommendations from the various chapters in this book will provide a basis for that change. The overall goal of this book is to provide the most current, concise, scientific appraisal of the efficacy of key foods and constituents medicines in dietary plants in preventing disease and improving the quality of life. While vegetables have traditionally been seen to be good sources of vitamins, the roles of other constituents have only recently become more widely recognized. This book reviews and often presents new hypotheses and conclusions on the effects of different bioactive components of the diet, derived particularly from vegetables, to prevent disease and improve the health of various populations.-* Identify bioactive fruit and vegetable options for prevention or treatment of illness * Moves from general overview to disease specific applications providing a framework for further research and deeper understanding * Includes discussion of issues and challenges, permitting critical analysis and evaluation.
Keywords: nutraceutika; výživa člověka; ovoce; zelenina; nutraceuticals; human nutrition; fruit; vegetables; elektronické knihy; electronic books